HR as a Strategic Partner in Business: An Effective Analysis in Current Scenario: Examining HR's Role as a Strategic Partner in Business (Journal of Advances and Scholarly Researches in Allied Education, 2018)
HR helps in different business companies in execution of their plans and business models. HR formulates the strategy with resource management. The HR they mainly occupied with the strategic plan in decision making. In this paper, the researcher has basically inspected how HR will be a strategic partner in business.